2019
DOI: 10.12669/pjms.35.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in the blend: Challenges faced by students enrolled in blended programs of Masters in Health Professions Education

Abstract: Objectives: The advent of computer technology and widespread use of internet has given rise to e-learning and blended programs all over the world. The aim of this study was to explore problems faced by students enrolled in blended program of MHPE in Pakistan. Methods: This was a qualitative exploratory study done between October 2017 and February 2018. Data included semi-structured individual interviews of eighteen students and four facilitators involved in blended MHPE programs of three leading Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Seven out of 24 papers reported factors that may be variants to learners' motivation and expectations to be able to meet their personal and professional needs and goals [44,45,47,50,55,56,60]. While analysing reported factors, two groups of factors appeared common, i.e.…”
Section: Barriers or Challenges Theme 5: Poor Motivation And Expectationmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven out of 24 papers reported factors that may be variants to learners' motivation and expectations to be able to meet their personal and professional needs and goals [44,45,47,50,55,56,60]. While analysing reported factors, two groups of factors appeared common, i.e.…”
Section: Barriers or Challenges Theme 5: Poor Motivation And Expectationmentioning
confidence: 99%
“…Nine out of 24 papers included in this review have reported that e-learning is a time-, cost-and labourintensive approach [44,45,47,50,53,55,56,60,63]. Several papers also raised the technological or IT challenges, as several learners are not familiar with e-learning and in some contexts, even basic IT knowledge and skills are lacking [44,45,53,55,56,63].…”
Section: Theme 6: Resource-intensivementioning
confidence: 99%
“…This method of teaching-learning is called 'blended learning' which has flourished equally in the developed and developing countries around the world because of its importance and result-oriented style (2) . The term consisting of two word, 'blend' and 'learning' denotes mixing of various approaches and methods (blend) and adaptation of various new information and knowledge (learning) (3) .…”
Section: Introductionmentioning
confidence: 99%
“…The programs and approaches blended in this method can provide with better opportunities of leaning in interactive manners amongst teachers and students, pedagogical abundance of elasticity and interaction, and cost-effective system to deliver the teaching and learning as meaningful and effective to their beneficiaries in the maximum quantity and quality (3) . Blended learning is an amalgamation of traditional and advanced learning approaches like in-class and out-of-class including as both the physical and virtual appearances of teachers and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation